Pembelajaran PAI sebagai Sarana Meningkatkan Kesejahteraan Jasmani, Mental, dan Spiritual Peserta Didik - Miftakhul Fahmy; Lu’luil Shilvia Muna Rosyidah; Bayu Dwi Pamungkas (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
Islamic Religious Education (PAI) plays a strategic role in supporting the holistic development of students, particularly in the context of achieving Sustainable Development Goal (SDG) 3 on mental health and well-being. This article discusses the contribution of PAI to improving students' mental, spiritual, and socio-emotional health through a values-based approach, religious practices, and religious character development. Various studies have shown that PAI can improve emotional regulation, reduce anxiety and stress levels, and develop spiritual coping mechanisms through the internalization of the concepts of tawakkal (trust), patience, gratitude, and self-control. Furthermore, PAI also plays a role in strengthening students' religious identity from an early age, resulting in increased self-discipline, a meaningful life orientation, and spiritual resilience. Socially, PAI learning contributes to creating a harmonious school environment through the formation of morals, the instilling of tolerance, and the strengthening of social interactions based on empathy and brotherhood. However, previous research has identified limitations in methodological aspects and curriculum implementation, necessitating the development of more contextual, adaptive, and evidence-based PAI learning models. Thus, the results of this study confirm that Islamic Religious Education (PAI) is a crucial element in creating students who not only excel academically but also possess balanced mental and spiritual well-being, in line with the goals of national education based on values ​​and humanization.